MCCALL'S SOFTWARE QUALITY METHOD FOR ENSURING THE QUALITY OF NEW STUDENT ADMISSION INFORMATION SYSTEM - Yayak Kartika Sari; Salma Salsabila Dwinta (STKIP PGRI TULUNGAGUNG, 2024)
New Student Admission (PMB) is a selection process for prospective students that is carried out regularly at a university. It generally involves a number of complex steps, such as collecting and verifying applicant data, assessing files, and announcing selection results. In today's digital era, many universities have adopted website-based admissions information systems to simplify the process of admitting new students. Bhinneka PGRI University is one of the universities that has implemented a website-based admissions information system using the pmb.ubhi.ac.id site. The purpose of this study was to test the feasibility of the admissions information system at Bhinneka PGRI University using the McCall Software Quality method. This research method involves collecting data through questionnaires that include five quality factors from the McCall method, namely accuracy, usability, integrity, reliability, and efficiency. The data was analyzed using a Likert scale to assess users' opinions on the quality of the application system. The results showed that this information system was able to increase staff efficiency in managing the selection process and the University's PMB file. Feasibility testing using the McCall method produces a percentage of 72.08%, which is in the range of 61% - 80% and is included in the good category.